Evoked potentials in pediatric cerebral malaria - Minal Bhanushali; Terrie E. Taylor; Malcolm E. Molyneux; Monica Sapuwa; Eunice Mwandira; Gretchen L. Birbeck (MDPI AG, 2011)
Cortical evoked potentials (EP) provide localized data regarding brain function and may offer prognostic information and insights into the pathologic mechanisms of malariamediated cerebral injury. As part of a prospective cohort study, we obtained somatosensory evoked potentials (SSEPs) and brainstem auditory EPs (AEPs) within 24 hours of admission on 27 consecutive children admitted with cerebral malaria (CM). Children underwent follow-up for 12 months to determine if they had any long term neurologic sequelae. EPs were obtained in 27 pediatric CM admissions. Two children died. Among survivors followed an average of 514 days, 7/25 (28.0%) had at least one adverse neurologic outcome. Only a single subject had absent cortical EPs on admission and this child had a good neurologic outcome. Among pediatric CM survivors, cortical EPs are generally intact and do not predict adverse neurologic outcomes. Further study is needed to determine if alterations in cortical EPs can be used to predict a fatal outcome in CM.